2004
DOI: 10.1136/jnnp.2003.010223
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal size and memory function in the ninth and tenth decades of life: the Sydney Older Persons Study

Abstract: Objectives: The purpose of this study was to define magnetic resonance imaging (MRI) correlates of normal brain ageing, with the specific objective of investigating whether the size of the hippocampus is selectively correlated with age related memory performance in non-demented individuals in their ninth and tenth decades of life. Methods: Hippocampal size was estimated using MRI based volumetry and qualitative visual assessment in 102 community dwelling individuals aged between 81 and 94 years. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 33 publications
4
41
0
Order By: Relevance
“…Concerning cognitive disabilities, our study shows that their prevalence increases with age, markedly so after 70 years, for concentration-attention, orientation, problem-solving, and memory. The alterations in cognitive function in the elderly can be caused by atrophy in certain cortical areas [35] or the hippocampus [36] and by modifi cation in neural plasticity [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning cognitive disabilities, our study shows that their prevalence increases with age, markedly so after 70 years, for concentration-attention, orientation, problem-solving, and memory. The alterations in cognitive function in the elderly can be caused by atrophy in certain cortical areas [35] or the hippocampus [36] and by modifi cation in neural plasticity [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported larger hippocampal volumes are associated with better memory performance [16][17][18][19] , though not all investigations have found this relationship [20] . Several studies, in fact, have found hippocampal volumes to be related to memory performance in cognitively impaired samples, but not in cognitively healthy participants [21][22][23] or more mildly impaired individuals, such as in age-associated memory impairment [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Although hippocampal atrophy assessed with visual rating scales in diagnostic and prognostic studies have proven to differentiate between patients with Alzheimer's disease and healthy controls (Scheltens et al, 1992;Wahlund et al, 2000;Bresciani et al, 2005)and other studies reported that rating scales predict memory performance in normal aging and in subjects with mild cognitive impairment (Korf et al, 2004;Lye et al, 2004;van de Pol et al, 2007), it is likely that measures of global or subcortical atrophy perform equally well. Also, volumetric measurements of the hippocampus may be the preferred method over rating scales if the objective is to examine whether hippocampal volume loss is disproportionate relative to other brain tissue loss, since this is generally considered to be the case in early stages of Alzheimer's disease (Laakso et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…The visual rating scales have demonstrated to correctly classify healthy controls and demented patients (Scheltens et al, 1992). Qualitative rating also has proven to be as sensitive as volumetric measurements in predicting memory performance in normal aging, suggesting that it may be a diagnostic tool for early detection of Alzheimer's disease in clinical practice (Lye et al, 2004). However, the correlation between the visual rating scores and the volume of the hippocampus described in previous reports is only moderate with a correlation coefficient between 0.27 and 0.42 (Wahlund et al, 1999;Visser et al, 2002).…”
Section: Introductionmentioning
confidence: 98%